Soccer and creatine, a systematic review - Monsalve Guevara, Víctor.; Montalva Valenzuela, Felipe.; Andrades Ramírez, Óscar Andrés.; Narrea Vargas, José Jairo.; Flores, Ito; Castillo Paredes, Antonio Jonathan. (Federación Española de Docentes de Educación Física, 2024)
Soccer is a collective sport, one of the most popular sports throughout the world. Therefore, the contribution of nutritional strategies is required for the optimal performance of the athlete. The objective of this systematic review is to analyze and describe through the scientific literature the effects of creatine consumption in soccer players. Through the Scopus, WoS, PubMed and SciELO databases, a total of 6 scientific articles were identified, which were found using the keywords "Soccer" OR "Football" AND "Creatine" AND "physical condition" OR "performance". Results related to "Creatine dose and intervention period", "Effects on the respiratory tract and respiratory volume", "Jump height", "Aerobic resistance", "Anaerobic power", "Sportsmanship", and "Speed" were found and address changes. Finally, the effectiveness of creatine consumption depends on the inclusion of a maintenance phase or not, allowing improvements in muscle power, speed and physical performance in soccer players.
Futbol y creatina, una revisión sistemática
Keywords: Condición física; Fútbol; Creatina; Rendimiento atlético